Instant preheating mechanism and ultrahigh energy cosmic rays - Campos, A. H.; Maia, JMF; Rosenfeld, R. (American Physical Soc, 2004)
Top-down models assume that the still unexplained ultrahigh energy cosmic rays (UHECR's) are the decay products of superheavy particles. Such particles may have been produced by one of the post-inflationary reheating mechanisms and may account for a fraction of the cold dark matter. In this paper, we assess the phenomenological applicability of the simplest instant preheating framework not to describe a reheating process, but as a mechanism to generate relic supermassive particles as possible sources of UHECR's. We use cosmic ray flux and cold dark matter observational data to constrain the parameters of the model.